Pengaruh Persepsi Harga, Kualitas Produk, dan Kepuasan Pelanggan Terhadap Minat Pembelian Ulang - Yudi Darma (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research was aiming to determine the effect of price perception, product quality and customer satisfaction on repurchase intention. The sampling technique used in this study is nonprobability sampling by convenience sampling. Sampling using a quantitative approach by distributing questionnaires to 126 respondents in Jakarta. For operational variables using the Likert scale. The data analysis method uses regression data analysis which is processed through the SPSS program. Based on the results of this study indicate that significant positive price perceptions, positive significant product quality, significant positive customer satisfaction on repurchase intention. In this research, price perception has the most influence on repurchase intention.